Algorithm for information protection in the auto-mated systems - Zhelyazova, Velqna; Nikolaev, Ivan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
This scientific report proposes Algorithm to protect information from unauthorized access (IPUA) in the automated systems (AS) with integrated procedures of analysis and synthesis. Currently, the insurance of the information safety (IS) in the automated systems for information processing in the management of different objects becomes a major importance. These objects include: telecommunication systems, banking systems, systems providing the work of the atom electro stations, systems for management of sea, air and land transport, systems for processing and storing of confidential and secret information [1, 2, and 9]. The high us-age of local, corporative and global networks with the appliance of open protocols for data transmission intensifies the problem with the information protection.